Inteligência artificial e suas implicações ético-jurídicas - Silva, Bárbara Jennifer Paz de Abreu da (2020)
Artificial intelligence (AI) has recently assumed a relevant role in the most diverse sectors of our society. We are at a point of no return, and our future will naturally pass through the incorporation of artificial intelligence, in our daily life, whether professional or personal. The idea of the existence of "thinking" machines that make decisions for humans raises a series of ethical questions that must be present when developing and implementing artificial intelligence in the most diverse sectors of society and especially in the regulation of AI. It is essential to study and investigate the best approaches for safe implementation and to address liability issues arising from the use of these technologies. This study identifies the main guiding principles of ethical regulation in the field of AI in the context of the use of intelligent and, above all, autonomous systems. It also presents an overview of the main fields in which AI is used and how it has impacted the Society.